Regional-scale patterns in harbour porpoise occupancy of tidal stream environments. (31st August 2017) - Waggitt, James J; Dunn, Holly K; Evans, Peter G H; Hiddink, Jan Geert; Holmes, Laura J; Keen, Emma; Murcott, Ben D; Piano, Marco; Robins, P E; Scott, Beth E; Whitmore, Jenny; Veneruso, Gemma
Abstract: As harbour porpoises Phocoena phocoena are abundant within tidal stream environments, mitigating population-level impacts from tidal stream energy extraction is considered a conservation priority. An understanding of their spatial and temporal occupancy of these habitats at a regional-scale will help steer installations towards locations which maximize energy returns but reduce the potential for interactions with populations. This study quantifies and compares relationships between the presence of harbour porpoise and several hydrodynamic characteristics across four tidal stream environments in Anglesey, UK—a region that has been earmarked for extensive industrial development. Within sites (0.57–1.13 km 2 ), encounters with animals were concentrated in small areas (<200 m 2 ) and increased during certain tidal states (ebb vs. flood). In sites showing relatively high maximum current speeds (2.67–2.87 ms −1 ), encounters were strongly associated with the emergence of shear-lines. In sites with relatively low maximum current speeds (1.70–2.08 ms −1 ), encounters were more associated with areas of shallow water during peak current speeds. The overall probability of encounters was higher in low current sites. It is suggested that the likelihood of interactions could be reduced by restricting developments to sites with high maximum current speeds (>2.5 ms −1 ), and placing turbines in areas of laminar currents therein. This study shows that a combination of local and regional hydrodynamic characteristics can partially explain variations in occupancy patterns across tidal-stream environments. However, it was found that such hydrodynamic characteristics could not comprehensively explain these occupancy patterns. Further studies into the biophysical mechanisms creating foraging opportunities within these habitats are needed to identify alternative explanatory variables that may have universal applications.